2007
DOI: 10.1136/ard.2006.061390
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 rs2004640-T allele, the new genetic factor for systemic lupus erythematosus, is not associated with rheumatoid arthritis

Abstract: Our results exclude the IRF5 rs2004640-T allele as a major genetic factor for RA in this French Caucasian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Equally however, there are also studies that do not agree with Irf5 associations with RA, so the link is not as robust as is observed with SLE (85,86).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 55%
“…Equally however, there are also studies that do not agree with Irf5 associations with RA, so the link is not as robust as is observed with SLE (85,86).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 55%
“…Using the binomial distribution, we had 88.5% power to detect a trend in favor of an association: probability of having the frequency in patients superior to that in controls following the binomial distribution for n observations (0-100 in our trio index) [13]. The Hardy-Weinberg equilibrium was checked in the control group (constituted by the nontransmitted parental chromosomes from trio) before analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic data support this model as several loci have been identified that are associated with the risk of both SLE and RA, including HLA haplotypes, BLK [162], PTPN22 [144], STAT4 [32], FCGR2A [192], PRDM1 [192] and TNFAIP3. IRF5 has also been shown to be associated with RA in some studies [193,194], however, others have failed to demonstrate an association [195,196]. Although these two diseases do share some overlapping phenotypes, many key features are distinct and, consistent with this, many loci appear to be associated exclusively with one disease and not the other [197].…”
Section: Overlap Of Sle With Other Autoimmune and Inflammatory Disordersmentioning
confidence: 98%